Structure, dynamics and selectivity in the sulfotransferase family. (11th September 2013) - Leyh, Thomas S.; Cook, Ian; Wang, Ting
Abstract: Combined structure, function and molecular dynamics studies of human cytosolic sulfotransferases (SULT1A1 and 2A1) have revealed that these enzymes contain a ∼30-residue active-site cap whose structure responds to substrates and mediates their interactions. The binding of 3′-phosphoadenosine 5′-phosphosulfate (PAPS) gates access to the active site by a remodeling of the cap that constricts the pore through which acceptors must pass to enter the active site. While the PAPS-bound enzyme spends the majority (∼95%) of its time in the constricted state, the pore isomerizes between the open and closed states when the nucleotide (PAPS) is bound. The dimensions of the open and closed pores place widely different steric constraints on substrate selectivity. Nature appears to have crafted these enzymes with two specificity settings – a closed-pore setting that admits a set of closely related structures, and an open setting that allows a far wider spectrum of acceptor geometries. The specificities of these settings seem well matched to the metabolic demands for homeostatic and defensive SULT functions. The departure of nucleotide requires that the cap open. This isomerization dependent release can explain both the product bursts and substrate inhibition seen in many SULTs. Here, the experimental underpinnings of the cap-mechanism are reviewed, and the advantages of such a mechanism are considered in the context of the cellular and metabolic environment in which these enzymes operate.